Impact of CALR and JAK2V617F Mutations on Clinical Course and Disease Outcomes in Essential Thrombocythemia: A Multicenter Retrospective Study in Turkish Patients - Zehra Narlı Özdemir; Yıldız İpek; Püsem Patır; Gözde Ermiş; Rafiye Çiftçiler; Deniz Özmen; Mehmet Baysal; Vildan Gürsoy; Esra Yıldızhan; Serkan Güven; Tarık Ercan; Tayfun Elibol; et al. (Turkish Journal of Hematology, 2024)
Objective: In this study, we investigated the effects of calreticulin (CALR) and JAK2V617F mutational status on clinical course and disease outcomes in Turkish patients with essential thrombocythemia (ET). Materials and Methods: Seventeen centers from Türkiye participated in the study and CALR- and JAK2V617F-mutated ET patients were evaluated retrospectively. Results: A total of 302 patients were included, of whom 203 (67.2%) and 99 (32.8%) were JAK2V617F- and CALR-positive, respectively. CALR-mutated patients were significantly younger (51 years vs. 57.5 years, p=0.03), with higher median platelet counts (987x109/L vs. 709x109/L, p<0.001) and lower median hemoglobin levels (13.1 g/dL vs. 14.1 g/dL, p<0.001) compared to JAK2V617F-mutated patients. Thromboembolic events (TEEs) occurred in 54 patients (17.9%), 77.8% of which were arterial. Compared to CALR mutation, JAK2V617F was associated with a higher risk of thrombosis (8.1% vs. 22.7%, p=0.002). Rates of transformation to myelofibrosis (MF) and leukemia were 4% and 0.7%, respectively, and these rates were comparable between JAK2V617F- and CALR-mutated cases. The estimated overall survival (OS) and MF-free survival of the entire cohort were 265.1 months and 235.7 months, respectively. OS and MF-free survival durations were similar between JAK2V617F- and CALR-mutated patients. Thrombosis-free survival (TFS) was superior in CALR-mutated patients compared to JAK2V617F-positive patients (5-year TFS: 90% vs. 71%, respectively; p=0.001). Age at diagnosis was an independent factor affecting the incidence of TEEs. Conclusion: In our ET cohort, CALR mutations resulted in higher platelet counts and lower hemoglobin levels than JAK2V617F and were associated with younger age at diagnosis. JAK2V617F was strongly associated with thrombosis and worse TFS. Hydroxyurea was the most preferred cytoreductive agent for patients with high thrombosis risk.